Rural Tourism and Socio-Economic Development in Kalapatta Sub County Kabong District of Uganda - Akorio, Fred Ariyon; Turyamureeba, Silaji; Tugume, Azarious; Eze, Val Hyginus Udoka (Journal of Humanities and Social Sciences (JHASS), 2024)
This research explores the interplay between rural tourism and socio-economic development in Kalapatta Sub County, located within the Kabong District. As rural areas globally seek sustainable pathways for growth, the study focuses on the specific impacts of tourism on the socio-economic fabric of the community. The research employs a mixed-methods approach, combining quantitative data analysis and qualitative insights gathered through interviews and surveys conducted among local residents, business owners, and tourists. Key indicators such as income generation, employment opportunities, infrastructure development, and cultural preservation are examined to assess the multifaceted impact of rural tourism on the local community. Preliminary findings indicate that the influx of tourists has led to increased economic activities, including the growth of local businesses and the creation of employment opportunities. However, challenges such as environmental degradation, cultural commodification, and unequal distribution of benefits are also identified. The research sheds light on the complex dynamics between the tourism industry and the socio-economic development of the rural community, emphasizing the need for sustainable and inclusive strategies. The study contributes to the existing body of knowledge on rural tourism by providing context-specific insights from Kalapatta Sub County, Kabong District. Recommendations for policymakers, local authorities, and community stakeholders are offered to guide the development of strategies that maximize the positive impacts of tourism while mitigating its potential negative consequences. Ultimately, this research aims to inform the creation of a framework for sustainable rural tourism that fosters socio-economic development in a manner that respects and enhances the local culture and environment